Analisis Antropometri Petani Dan Aplikasinya Pada Desain Alat Pemanen Manggis - Sella Fiana; Wahyu Kristian Sugandi; Ahmad Thoriq; Asep Yusuf (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2019)
Harvesting of mangosteen is manually by climbing trees or using simple harvesting tools that made from bamboo. In order to increase productivity, it is necessary to design mangosteen harvesting equipment by referring to harvesting anthropometry. Anthropometric data were collected from 30 (thirty) mangosteen harvesters which included height, shoulder height, knee height, arm length, hand reach up to grip, front hand reach, palm length, index finger and thumb diameter to the middle finger. The making of the tool refers to the 5th percentile data to get the maximum dimension of the tool for farmers who have SMAll and comfortable bodies for those who have large bodies. The results showed that the average harvesting height was 150 cm, shoulder height 125 cm, knee height 37.92 cm, arm length 47.62 cm, hand reach above grip 177.54 cm, forward hand reach 65.67 cm, the front hand reaches 59.45 cm, the thumb grip diameter to the index finger 37.70 mm, and the thumb grip diameter to the middle finger is 44.17 mm. Based on the anthropometric data, the design of the harvesting equipment was obtained using a telescopic system with a length of 3 m which can be shortened to 1.5 m, the diameter of the handle 3.2 cm, and the shape of the mangosteen fruit resembling the letter “V” with an aluminium plate construction.